SEASONALLY SPECIFIC RESPONSES OF THE EAST ASIAN MONSOON TO DEGLACIAL CLIMATE CHANGES - Nakagawa T.; Tarasov P.E.; Kitagawa H.; Yasuda Y.; Gotanda K. (My University, 2006)
The deglacial meltwater pulse in the North Atlantic that induced the Younger Dryas event also prompted climate cooling in East Asian monsoon regions such as Japan and coastal midlatitude China. However, very little is understood about the mechanism that can transmit changes in the North Atlantic to the Far East. Here we show that the shutdown of the North Atlantic thermohaline circulation brought about significantly lower temperatures and higher precipitation in the Japanese winter, whereas the change in the Japanese summer climate was considerably smaller. The cooling of the Siberian air mass seems to have caused an increased pressure gradient between Siberia and the West Pacific in winter, intensifying the winter monsoon. The Mongolian high-pressure system and the westerly jet stream played an important role in the teleconnection. In contrast, the warming at the onset of the late glacial interstadial (GI-1; Bølling-Allerød) in the West Pacific did not have season-specific features, implying that the principal driving mechanism of this warming event may lie in a panhemispheric or global factor, such as insolation changes. © 2006 Geological Society of America.
Keywords: DEGLACIATION; MONSOON; PALEOCLIMATOLOGY; PALYNOLOGY; SEASONAL VARIABILITY; YOUNGER DRYAS